E- Module Statistics Integrated with Tajweed Science on Surah Al-Kahf: E- Module Statistik Terintegrasi Ilmu Tajwid Pada Surat Al-Kahfi - Nurmitasari , Nurmitasari; Khasanah , Binti Anisaul; Astuti, Robia; Purnamasari , Wiwin; Nurmutoharoh , Nurmutoharoh; Syahaputra , Tegar Ilham (Universitas Muhammadiyah Sidoarjo, 2023)
The online learning process that occurred during the pandemic had a positive impact on teachers and students who had to adapt to technology and students were also trained to learn independently. This condition provides a great opportunity to develop interactive e-modules for learning, including mathematics learning. Pringsewu Muhammadiyah Middle School is a school that prioritizes Al-Islam and Muhammadiyah (AIK). The integration of AIK in mathematics learning is very suitable for this school. The knowledge of recitation contained in Surah Al-Kahf is presented and analyzed in the statistical knowledge contained in the e-module, which is a form of integration of AIK in mathematics. The aim of this research is to produce an integrated statistical e-module on Tajwid science in Surah Al-Kahf that is feasible and effective and it is hoped that this e-module can also teach Tajwid science to students. This type of research is development research which refers to the 4-D development model, namely Define, Design, Develop and Disseminate. The data collection instrument used was an expert assessment sheet for e-modules which included material experts, learning media and communication, curriculum design, AIK and users (teachers); student activity observation sheet; student response questionnaires and learning outcomes tests. The results of this research are that the integrated e-module of recitation science in Surah Al-Kahf is considered feasible based on expert assessments and is considered effective based on indicators of student activity, student responses, and student learning outcomes, with the percentage of active students being 100%, the percentage of positive responses students amounted to 96% and the percentage of students who obtained learning outcomes above the KKM was 96%. It is also hoped that the results of this research can be used as reference material for further research to develop similar products with different materials.